Deficiency of Lysosomic Acid Lipase: Clinical Recommendations for Child Health Care Delivery - A. A. Baranov; L. S. Namazova-Baranova; O. S. Gundobina; S. V. Mikhailova; E. U. Zakharova; E. A. Vishnyova; K. V. Savostianov; M. U. Stepanyan (Педиатрическая фармакология, 2016)
The deficiency of lysosomic acid lipase is a rare hereditary enzymopathy. The focus of this article is the present condition of this issue. The authors demonstrate epidemiological data and etiopathogenetic features of two phenotypic forms of lysosomic acid lipase deficiency — Wolman disease and cholesterol ester storage disease. Clinical features of both — the rapidly progressing form and the slowly developing cholesterol ester storage disease — are described in detail in this article. The algorithm and crucial steps of differential diagnosis are described in detail. Also, indications to pathogenetic therapy are carefully formulated, and the tactic of enzyme replacing therapy is given. The modern approaches to the management of child patients are described.